Analisis Metode Camel: Perbandingan Kinerja Keuangan Perbankan Syariah di Indonesia - Muhammad Imran (IAIN Kendari, 2022)
This study aims to compare the financial performance of Bank Muamalat Indonesia, Bank Mega Syariah and Bank Syariah Mandiri in terms of capital (capital), asset quality (asset quality), management (management), earnings (income) and liquidity (liquidity) using the CAMEL method. This is a quantitative comparative descriptive research with data collection techniques, namely by using the SPSS tool to search for data or financial statements already in each bank. This study shows that based on the results of data analysis, it can be obtained that the financial performance between Bank Muamalat Indonesia, Bank Mega Syariah and independent Islamic banks, the ratio of CAR, KAP, ROA, and LDR of Bank Mega Syariah is better than Bank Syariah Mandiri and Bank Muamalat Indonesia. While the NIM and BOPO ratios of Bank Syariah Mandiri are better than Bank Mega Syariah and Bank Muamalat Indonesia.